Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/2193-1801-3-305
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood development: the role of community based childcare centres in Malawi

Abstract: BackgroundSomatic changes including growth and development of the brain of a human being occur very early in life. Programmes that enhance early childhood development (ECD) therefore should be part of the national agenda. Cognizant of this fact, the Malawi Government together with development partners facilitated the establishment of community-based child care centres (CBCCs) which are owned and managed by community members. This study was aimed at understanding how CBCCs operated and their core functions.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 5 publications
(6 reference statements)
0
31
0
2
Order By: Relevance
“…Some supervision by senior HSAs does exist but is not incentivized or competency based. Malawi is one of the first African countries to have ECD support through Community‐Based Child Care Centers for 3–5 years old supported by Ministry of Gender, Children, Disability and Social Welfare . This does not support children younger than 3 …”
Section: Introductionmentioning
confidence: 99%
“…Some supervision by senior HSAs does exist but is not incentivized or competency based. Malawi is one of the first African countries to have ECD support through Community‐Based Child Care Centers for 3–5 years old supported by Ministry of Gender, Children, Disability and Social Welfare . This does not support children younger than 3 …”
Section: Introductionmentioning
confidence: 99%
“…As an example, Munthali et al (2014) found that CBCCs were reluctant to enrol children with 'special needs' because of a 'lack of appropriate training and resources' (p. 4). Further, they report that caregivers did not register children who were unable to communicate 'mainly because [they] may fail to interact well with his or her friends and caregivers' (p. 5) and tended to turn away children who they considered to have behaviour problems.…”
Section: Application Of the Inclusive Early Childhood Development Modmentioning
confidence: 99%
“…Malawi was one of the first African countries to have a network of CBCCs for young children (3-5 years) supported by Ministry of Gender, Disability and Social Welfare (MGCDSW). Whilst CBCCs provide an early learning environment to children living nearby, it is reported that the quality of most of the CBCCs, measured in terms of buildings, sanitation facilities, staff numbers, capacity, materials and equipment, has fallen short of the early childhood development Monitoring and Evaluation Framework set out by the MGCDSW (Munthali et al 2008).…”
Section: Application Of the Inclusive Early Childhood Development Modmentioning
confidence: 99%
“…The recent government Growth and Development Strategy addresses the need for integrated ECD and aims to increase the number of CBCCs and children with disabilities attending CBCCs (The Ministry of Economic Planning and Development, ). At present, there is little evidence on how they support children with disabilities or special needs who attend (Munthali & Silo, ).…”
Section: Methodsmentioning
confidence: 99%